Scholarly Communication and Academic Presses - Anna Maria, Tammaro (Proceedings e report, 2002)
The objective of the meeting was to identify concrete ways for implementing proposals to foster the international scientific co-operation of universities and academic societies. Against the background of an assumed tendency towards knowledge monopolies, caused by the protection of intellectual property rights by a few publishers, the experts in the Conference discussed the potential of these academic e-presses for improving scientific article collection and treatment as well as facilitating the access to scientific knowledge. The papers in this volume can best be regarded as contributions to the areas of inquiry in a field that is continuing to change very rapidly.